Neuronal mechanisms of epileptogenesis - Roberto Di Maio (Frontiers Research Topics, 2015)
Several types of brain injuries are causes of acquired temporal lobe epilepsy (TLE). The seizure-free "latent period" that often follows the brain injury is of unknown mechanistic significance but is commonly considered as the "epileptogenic" period characterized by gradual pathogenic processes leading to the onset of clinically detectable epilepsy. Acute convulsive status epilepticus (SE) is often associated with an adverse developmental outcome characterized by learning disabilities related to the cumulative effects of seizures and development of TLE. The symptomatic manifestations of TLE appear only after a widespread irreversible damage of entorhinal cortex, and hippocampus, the brain area most affected by this disease. These pathological features of TLE reduce the possibility of successful therapeutic approaches, often rendering the disease refractory. The difficult clinical management of chronic TLE and the limited success rate of surgical approaches, increase the incapacitating nature of this specific epileptic disorder. Prevention of TLE with an appropriate intervention after a known inciting event (in the case of acquired epilepsy) might represent the most ambitious goal in the clinical treatment of this epileptic disorder, but has been largely unsuccessful to this point. Clinical trials aimed at prevention of chronic epilepsy have often produced negative, disappointing results. However, in most cases, these studies ultimately evaluated the downstream clinical manifestations, failing to monitor early, specific molecular epileptogenic events. Therefore, elucidation of the underlying mechanisms of epileptogenesis, and their time course(s) are essential. The primary purpose of this topic is to collect scientific contributions providing novel insights in the cellular and molecular mechanisms of epileptogenesis as potential targets for innovative therapeutic approaches aimed at preventing the chronic epileptic disorder.